Protein–GAG interactions: new surface-based techniques, spectroscopies and nanotechnology probes. (22nd May 2006) - Yates, E.A.; Terry, C.J.; Rees, C.; Rudd, T.R.; Duchesne, L.; Skidmore, M.A.; Lévy, R.; Thanh, N.T.K.; Nichols, R.J.; Clarke, D.T.; Fernig, D.G.
Abstract : New approaches, rooted in the physical sciences, have been developed to gain a more fundamental understanding of protein–GAG (glycosaminoglycan) interactions. DPI (dual polarization interferometry) is an optical technique, which measures real-time changes in the mass of molecules bound at a surface and the geometry of the bound molecules. QCM-D (quartz crystal microbalance-dissipation), an acoustic technique, measures the mass and the viscoelastic properties of adsorbates. The FTIR (Fourier-transform IR) amide bands I, II and III, resulting from the peptide bond, provide insight into protein secondary structure. Synchrotron radiation CD goes to much shorter wavelengths than laboratory CD, allowing access to chromophores that provide insights into the conformation of the GAG chain and of β-strand structures of proteins. To tackle the diversity of GAG structure, we are developing noble metal nanoparticle probes, which can be detected at the level of single particles and so enable single molecule biochemistry and analytical chemistry. These new approaches are enabling new insights into structure–function relationships in GAGs and together they will resolve many of the outstanding problems in this field.